Publish or Perish - Yudkevich, Maria (International Higher Education, 2020)
This article considers the causes and consequences of the increasing role of the “publish or perish” principle in modern academic systems. In particular, it discusses how various types of universities interpret this principle and why its causes differ across academic systems.